Γδ T Cells Promote Steatohepatitis by Orchestrating Innate and Adaptive Immune Programming. Issue 2 (31st December 2019) - Torres‐Hernandez, Alejandro; Wang, Wei; Nikiforov, Yuri; Tejada, Karla; Torres, Luisana; Kalabin, Aleksandr; Adam, Salma; Wu, Jingjing; Lu, Lu; Chen, Ruonan; Lemmer, Aaron; Camargo, Jimmy; et al.
Abstract : Background and Aims: The recruitment and activation of inflammatory cells in the liver delineates the transition from hepatic steatosis to steatohepatitis (SH). Approach and Results: We found that in SH, γδT cells are recruited to the liver by C‐C chemokine receptor (CCR) 2, CCR5, and nucleotide‐binding oligomerization domain‐containing protein 2 signaling and are skewed toward an interleukin (IL)‐17A + phenotype in an inducible costimulator (ICOS)/ICOS ligand–dependent manner. γδT cells exhibit a distinct Vγ4 +, PD1 +, Ly6C + CD44 + phenotype in SH. Moreover, γδT cells up‐regulate both CD1d, which is necessary for lipid‐based antigens presentation, and the free fatty acid receptor, CD36. γδT cells are stimulated to express IL‐17A by palmitic acid and CD1d ligation. Deletion, depletion, and targeted interruption of γδT cell recruitment protects against diet‐induced SH and accelerates disease resolution. Conclusions: We demonstrate that hepatic γδT cells exacerbate SH, independent of IL‐17 expression, by mitigating conventional CD4 + T‐cell expansion and modulating their inflammatory program by CD1d‐dependent vascular endothelial growth factor expression.